PROSPECTIVE DIRECTIONS OF FUND MARKET DEVELOPMENT IN UZBEKISTAN - Burxonov Sardorjon Nasulloyevich; Bobomurodov Kayimjon Homidovich (Лучшие интеллектуальные исследования, 2024)
Annotation. In this, the development of all branches and sectors of the economy is directly related to the development of the real sector and the production sector, the development of the economy of Uzbekistan and the stock market. The analysis of the modern state of the stock market of Uzbekistan and development has been carried out, and there will be issues of further improvement of the new stock market, which will be subject to regulatory-legal, institutional, organizational-economic conditions at the state level for the practical application of the stock market in our economy. a number of scientific proposals and practical recommendations are given, and an analytical opinion about the recommendations on this topic.